Efektivitas Pembelajaran Statistika Melalui Pendekatan Kontekstual Pada Siswa Kelas XII IPS Man 2 Halmahera Utara - Kurnia A. Saleh; Sitna Maryam Saleh (EDUKASI, 2023)
Statistics is a branch of applied mathematics that discusses scientific methods, procedures for collecting and classifying data, compiling and presenting data, arriving at valid conclusions, so that decisions are taken that are acceptable. The goal to be achieved from this research is to find out the activities and learning outcomes of students in cycles I and II. This research is a Classroom Action Research (CAR), and was carried out at MAN 2 Halut in class XII IPS, with a total of 20 students. The minimum completeness criterion (KKM) in the mathematics subject set at Madrasah Aliyah Negeri 2 Halmahera Utara is 78. Data analysis was carried out by determining student learning completeness individually and classically, and determining the percentage of student activity and learning outcomes in cycles I and II. The results showed that the learning activities of students in class XII IPS MAN 2 North Halmahera related to mathematics learning activities, especially the subject of statistics through a contextual approach which were observed as a whole, could be categorized as very effective. There is an increase in student learning outcomes in class XII IPS MAN 2 North Halmahera in mathematics, especially the subject of statistics through a contextual approach, both cycle I and cycle II have achieved the KKM set by the school and are categorized as good.